Economic evaluation of specially protected natural areas (Eurasian Journal of Ecology, 2018)
There is a significant change in the organization and development ofspecially protected natural territories nowadays. The main priority directions of «green» economy are taken into account in the process of theirorganization and development. The results of the analysis in the articleshow that methods of total economic value are important at economicevaluation of protected areas, because methods of total economic valueare an effective tool in the evaluation of resources, especially in protectednatural territories. The article gives a brief description of the specially protected natural territories of the Republic of Kazakhstan. Currently, speciallyprotected natural territories of the Republic are not have only a researchand educational interest, but also it’s the single system provider of environmental services as a whole. Thus, within the framework of the green economy methods of economic evaluation of resources of specially protectednatural areas have an innovative character and are used in the evaluationof biological resources.Key words: specially protected natural areas, economic evaluation,recreation, value, natural resources,ecosystem services